Applicability and comparison of the sub-Saharan Africa and original WHO maternal near-miss criteria in a rural hospital in Western Tanzania - Olivier E van der Cammen; Steve P Chobo; Justine S Kasitu; Ipyana Mwampagatwa; Rob Mooij; Myrrith H Hulsbergen (Journal of Global Health Reports)
# Background After the introduction of the maternal near-miss (MNM) criteria by the World Health Organization (WHO), an adapted version for low-income countries was defined but has never been validated in a rural hospital in this setting. Aim of this study was to identify the occurrence of MNM by both the use of the WHO and the adapted sub-Saharan Africa (SSA) MNM tool and to compare the applicability of both versions.